2021
DOI: 10.1016/j.jss.2021.111089
|View full text |Cite
|
Sign up to set email alerts
|

An empirical study of COVID-19 related posts on Stack Overflow: Topics and technologies

Abstract: The COVID-19 outbreak, also known as the coronavirus pandemic, has left its mark on every aspect of our lives and at the time of this writing is still an ongoing battle. Beyond the immediate global-wide health response, the pandemic has triggered a significant number of IT initiatives to track, visualize, analyze and potentially mitigate the phenomenon. For individuals or organizations interested in developing COVID-19 related software, knowledge-sharing communities such as Stack Overflow proved to be an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Stack Overflow is another platform for data scientists and software developers. Georgiou et al [11], the Stack Overflow platform has been analyzed with web mining technique to present the most prominent technologies adopted for developing COVID-19 software. The results have shown that developers community response were immediate and the interest of developers on COVID-19 related challenges was sustained after its initial peak.…”
Section: Introductionmentioning
confidence: 99%
“…Stack Overflow is another platform for data scientists and software developers. Georgiou et al [11], the Stack Overflow platform has been analyzed with web mining technique to present the most prominent technologies adopted for developing COVID-19 software. The results have shown that developers community response were immediate and the interest of developers on COVID-19 related challenges was sustained after its initial peak.…”
Section: Introductionmentioning
confidence: 99%